உலகப்பழங்குடிகள் தமிழ்க்குடித்தமிழரின் மெய்ஞான நுண்ணறிவு: The Spiritual–Philosophical Wisdom of the Tamil Ethnic Community among the World’s Indigenous Peoples - Yokeswaran, T (Journal of Indian Studies (இந்திய ஆய்விதழ்), 2025)
Since the Earth’s formation over 4.6 billion years ago, no life forms appeared on Earth for the first 2.5 billion years. It remained a lifeless environment without living conditions, similar to the Moon, Mars, and other celestial bodies. Geologists have divided this vast period into four divisions. It is stated that humans originated before 1 million years BCE, and that the human race first emerged in Lemuria, which was located south of South India. They are said to be the aboriginal inhabitants of Tamil Nadu. Their racial similarity, physical anatomical similarity, and language structure are all similar to the Maori people who are the aboriginals living in New Zealand, as well as the Dayaks who are the aboriginal people of Indonesia, Polynesia, and the island of Borneo, and the Kadar people who are the tribal inhabitants of the Anaimalai hills—their use of the boomerang hunting weapon that returns and their tree-climbing methods are identical. One can understand that the first human race to appear in the world was the dark-skinned Tamil race, and that those who branched off from the Tamil race that originated in Lemuria became the Negroes. They have also migrated to the African continent. It becomes clear that regions such as Australia (Athireyar), Antarctica, South America, Madagascar, India, and others were inhabited by ancient Dravidian people during the Paleolithic period. Therefore, the world’s aboriginal peoples are Tamil people! உலகம் தோன்றிசு மார் 460 கோடி ஆண்டுகளுக்கும் மேலானநிலையில்முதல் 250 கோடி ஆண்டுகள் வரை உலகில் எந்த உயிரினமும் தோன்றவில்லை. அது உயிர்களற்ற சந்திரன், செவ்வாய் கிரகம் மற்றும் பிற இருப்பது போல உயிர்களற்ற வாழும் சூழலற்றநிலையே இருந்துள்ளது. இந்த நெடுங்காலத்தை நான்கு பிரிவுகளாகப் பிரித்தனர், நிலவியலாளர்கள். கி.மு. 10 இலட்சம் ஆண்டுகளுக்கு முற்பட்ட காலத்தில் மாந்தன்தோற்றம் எனவும் தென்னிந்தியாவிற்குத் தெற்கிலுள்ள லெமுரியாவில் தான் முதன்முதலில் மக்களினம் தோன்றிற்று. அவ்வினமே தமிழ்நாட்டின் ஆதிகுடிகள் எனவும் கூறுகின்றனர். இவர்களின் இனஒற்றுமை, மக்கள் உடல்கூறு ஒற்றுமை,மொழி அமைப்பு யாவும் நியுசிலாந்தில் வாழும் ஆதிகுடிகளான மேவோரி, மக்களும் இந்தோனேசியா, பாலினிசியாவிலும், போர்னியாதீவின்ஆதிகுடிகளானடையாக்களும், எய்யுங்,பூமராங் என்னும் மீண்டுவரும் வேட்டைக்கத்தியையும் ஆணைமலையின் பழங்குடிகளான காடர்களும், மரமேறும் முறை ஒரேவிதமாக உள்ளது. உலகில்தோன்றிய முதல் மனித இனம் கறுத்த தமிழர் இனமே என்பதையும், லெமுரியாவில் தோன்றிய தமிழர் இனத்திலிருந்து கிளைத்துச் சென்றவர்களே. நீக்ரோவர்கள் என்பதும் உணரலாம். ஆப்பிரிக்கக் கண்டத்திற்கும் இடம் பெயர்ந்துள்ளனர். ஆஸ்திரேலியா (ஆத்திரேயர்) அண்டார்டிக், தென் அமெரிக்கா, மடகாஸ்கர், இந்தியா, முதலிய பகுதிகள் பலியோ சோலிக்காலத்தில் பழந்திராவிடமக்களால் கலந்திருந்தது என்பதைத் தெளிவுரலாம். எனவே, உலகப் பழங்குடிகள் தமிழ்க்குடிமக்களே!